Pembelajaran Membaca Berbasis Pendidikan Karakter - Tania Amara Br. Pakpahan; Almi Waina; Farhan Syaukani (Universitas Dehasen Bengkulu, 2022)
Character education has an essence whose purpose is to shape the child's personality so that he becomes a good human being, society and citizen. Reading is one of the important language skills in education, especially in elementary school. This is because reading skills are a means to learn other subjects. It is said that because learning anything always requires reading skills. Beginning reading is given in grades I and II of elementary school. Beginning reading learning begins with reading without books, then continues with reading using books. Beginning reading learning is carried out by integrating character values. In reading activities, a person must activate his mind to be able to identify language, understand it, and interpret its meaning so that the message from what we have read is clearly captured